Horizons of a literary text interpretation in the folklore versions: Dying of Nemirovich-Danchenko - Трубицына, Виктория (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
This article defines the originality of the poem by Nemirovich-Danchenko Dying (1882) in the context of literary traditions of Russian gaol songs and poems about imprisonment. The directions of the reception and variation have been analyzed. The focus is also on the aesthetic principles and techniques of reproduction of a literary source in folk song culture in the Kemerovo region and its folklore.